The Baby Box scheme in Scotland: A study of public attitudes and social value - Zoë Skea; Agata Kostrzewa; Louise Locock; Mairead Black; Heather M. Morgan; Mandy Ryan (Wiley, 2022)
Abstract Background The Scottish Government introduced a free Baby Box scheme for all new parents in 2017, modelled on the Finnish scheme, to give every baby 'an equal start in life'. There is little evidence that it results in better health outcomes, but there has been limited research into different perspectives and discourses on such schemes. Methods Four focus groups were conducted with 21 parents in North‐East Scotland. Recordings were transcribed verbatim, anonymized and analysed thematically with NVivo 12 software. Our thematic analysis was both inductive and deductive-remaining open to themes identified by participants themselves but also informed by the social policy literature on universalism and social cohesion. Results Across all the focus groups, we found a high degree of positivity about the principle of the Baby Box scheme, and for the most part the practical value of the contents. This was remarkably consistent across different communities and backgrounds. There was little evidence of the strongly polarized views present in media reporting. Parents seemed considerably less focused than the media on safety and health outcomes, and more focused on practical, material and social impacts. They reported little in the way of feeling patronized or monitored by the government. Conclusion Our findings have important implications for future economic evaluations of the baby box. Such evaluations should broaden the valuation space beyond health outcomes to allow for the value of feelings of inclusion, solidarity and being part of a community. Patient or Public Contribution This small project was designed in response to parent views already collected in the early roll‐out of the Baby Box scheme in Scotland, about their priorities and responses to the scheme. Additional views were sought on the topic guide for the focus groups, and local community groups advised us on recruitment and the best timing and location for the focus groups to be held. The focus groups themselves were conducted as research, but with the intent of ensuring parent views featured more prominently in a debate that has been largely dominated by clinical and public health perspectives.